Performance Improvement of Dye-Sensitized Solar Cell- (DSSC-) Based Natural Dyes by Clathrin Protein - Prihanto Trihutomo; Sudjito Soeparman; Denny Widhiyanuriyawan; Lilis Yuliati (International Journal of Photoenergy)
Dye-Sensitized Solar Cell (DSSC) is a solar cell device that works using electrochemical principles in which sensitive dyes are absorbed in the TiO2 photoelectrode layer. The problem of DSSC-based natural dyes is the lower efficiency than silicon solar cells. This low efficiency is due to the barrier of electron transfer in the TiO2 semiconductor layer. In this study, the addition of clathrin protein to the TiO2 layer was used to increase electron transfer in the semiconductor layer resulting in improved DSSC performance. Clathrin is a protein that plays a role in the formation of transport vesicle membrane in eukaryotic cells. The method used in this study is clathrin protein with a concentration of 0%, 25%, 50%, and 75% added to TiO2 in DSSC structure. Photovoltaic characteristics of DSSC were measured using a data logger to determine the performance of DSSC, layer morphology was analyzed using Scanning Electron Microscopy (SEM), the element content in DSSC was analyzed using Energy-Dispersive X-ray Spectroscopy (EDS), and functional groups in DSSC layers were analyzed using Fourier-Transform Infrared Spectroscopy (FTIR). The result of this study is the addition of clathrin protein can improve DSSC performance, which resulted in the highest performance of DSSC on 75% clathrin protein addition with efficiency=1.465%, Isc=5.247 mA, and Voc=657 mV. From the results of SEM analysis, it appears that clathrin protein molecules fill the cavities in TiO2 molecules. EDS analysis shows an increase in carbon, oxygen, and phosphorus content in TiO2 layers with increasing clathrin protein concentration. FTIR analysis shows an increasingly sharp absorption in the FTIR spectrum of protein-forming functional groups by increasing clathrin protein concentration in DSSC.